2015
DOI: 10.1088/0964-1726/24/11/115029
|View full text |Cite
|
Sign up to set email alerts
|

Road roughness evaluation using in-pavement strain sensors

Abstract: The international roughness index (IRI) is a characterization of road roughness or ride quality that transportation agencies most often report. The prevalent method of acquiring IRI data requires instrumented vehicles and technicians with specialized training to interpret the results. The extensive labor and high cost requirements associated with the existing approaches limit data collection to at most once per year for portions of the national highway system. Agencies characterize roughness only for some seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In this paper above, some studies on how to calculate the ADV values and how to choose the sampling frequency and time-window are conducted. But according to Equation (11), it can be found that the mean square values of unsprung mass acceleration of vehicle suspension system are not only related to road roughness, sampling frequency, and timewindow in reality, but also has a direct relationship with the amplitude-frequency characteristics of vehicle suspension itself. µ -3σ at G q (n 0 ) = 22.6 × 10 -6 µ -3σ at G q (n 0 ) = 25.4 × 10 -6 µ -3σ at G q (n 0 ) = 32.0 × 10 -6 µ -3σ at G q (n 0 ) = 64.0 × 10 -6 µ 0 + 3σ 0 = µ -3σ * * * * * With wide use of semiactive suspension, in a vehicle suspension system, only the sprung mass, spring stiffness, and damping coefficient can be changed considerably.…”
Section: Analysis Of the Variation Of Adv Values With Suspension Paramentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper above, some studies on how to calculate the ADV values and how to choose the sampling frequency and time-window are conducted. But according to Equation (11), it can be found that the mean square values of unsprung mass acceleration of vehicle suspension system are not only related to road roughness, sampling frequency, and timewindow in reality, but also has a direct relationship with the amplitude-frequency characteristics of vehicle suspension itself. µ -3σ at G q (n 0 ) = 22.6 × 10 -6 µ -3σ at G q (n 0 ) = 25.4 × 10 -6 µ -3σ at G q (n 0 ) = 32.0 × 10 -6 µ -3σ at G q (n 0 ) = 64.0 × 10 -6 µ 0 + 3σ 0 = µ -3σ * * * * * With wide use of semiactive suspension, in a vehicle suspension system, only the sprung mass, spring stiffness, and damping coefficient can be changed considerably.…”
Section: Analysis Of the Variation Of Adv Values With Suspension Paramentioning
confidence: 99%
“…Existing methods for estimating road roughness can be divided into three categories [6]: direct measurements [7][8][9][10][11], noncontact measurements [12][13][14][15], and system response-based estimation [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large dynamic axle loading from roughness accelerates pavement deterioration, so pavement engineers have to maintenance the road in relatively good level all the time [1]. However, analysis and measurement of road roughness is a difficult problem that pavement engineers have been facing for many years, especially the road which heavy vehicles such as truck often make lots of stop-and-go trips [1]. Detection and maintenance of the condition of a road profile is important for many reasons, such as safety and economic savings.…”
Section: Introductionmentioning
confidence: 99%
“…Currently applied road estimation methods can be roughly divided into three categories [5], i.e. direct measurement [5,6], non-contact measurement [7,8] and system response-based estimation [9,10]. Among these, due to lower costs and reduced measurement contamination (e.g.…”
Section: Introductionmentioning
confidence: 99%